Predicting the risk of malaria importation into Jiangsu Province, China: a modeling study - Liu, Kaixuan; Cao, Yuanyuan; Xu, Enyu; Chong, Zeyin; Chai, Liying; Wang, Yi; Xu, Yuhui; Wang, Yin; Zhang, Jun; Müller, Olaf; Cao, Jun; Zhu, Guoding; et al. (Globalization and health, 2024)
The World Health Organization certified China malaria-free in 2021. Consequently, preventing the risk of malaria re-introduction caused by imported malaria has now become a major challenge. This study aims to characterize the dynamics and predict the risk of malaria importation in Jiangsu Province, where the number of imported malaria cases ranks among the highest in China.
Gesehen am 30.06.2025